Elasticity theory: 13.4. bis 19.4.1986 - Ball, John M.; Jäger, Willi (Tagungsbericht, 1986)
Martin Costabel, Darmstadt; Stuart Antman, College Park; Bernard Dacorogna, Lausanne; Gabriele Anzellotti, Povo; Ulrich Dierkes, Saarbrücken; J. M. Ball, Edinburgh; Irene Fonseca, Lisboa; Herbert Beckert, Makkleeberg; Jens Frehse, Bonn; Dietrich Braess, Bochum; Martin Fuchs, Düsseldorf; Philippe Ciarlet, Paris; Joachim Gwinner, Darmstadt; Stefan Hildebrandt, Bonn; Stephan Luckhaus, Heidelberg; W. Jäger, Heidelberg; E. Meister, Darmstadt; Jozef Kačur, Bratislava; Alexander Mielke, Stuttgart; Bernhard Kawohl, Heidelberg; Victor J. Mizel, Pittsburgh; Christian Klingenberg, Heildelberg; Ingo Müller, Berlin; R. J. Knops, Edinburgh; S. Müller, Riccarton; Robert Kohn, New York; Francois Murat, Paris; Jindrich Nečas, Prag; Luc Tartar, Villeneuve Saint-Georges; Reinhard Racke, Bonn; Friedrich Tomi, Heidelberg; M. Reeken, Wuppertal; Waldemar Velte, Würzburg; J. Sivaloganathan, Bath; Wolf von Wahl, Bayreuth; Scott J. Spector, Carbondale; Peter Weidemaier, Bayreuth; Erwin Stein, Hannover; Michael Wiegner, Bayreuth; C. A. Stuart, Lausanne; E. Zehnder, Bochum-Querenburg